NEGARA, AGAMA, DAN MODERASI: KAJIAN POLITIK HUKUM REGULASI KERUKUNAN UMAT BERAGAMA DI INDONESIA - Wawan Saputra (AL-BALAD : Jurnal Hukum Tata Negara dan Politik Islam, 2025)
This study analyzes the legal policies governing interfaith harmony in Indonesia from the perspective of the relationship between the state, religion, and religious moderation. As a multicultural nation, Indonesia faces significant challenges in maintaining social harmony amid religious and ideological diversity. Various regulations regarding interfaith harmony have been established to maintain social stability and prevent religion-based conflicts. However, in practice, a number of these regulations still pose problems, particularly regarding the protection of religious freedom and the potential for discrimination against minority groups. This study aims to analyze the legal policy direction of regulations on interfaith harmony and to examine the relevance of religious moderation as a paradigm in the formulation and implementation of legal policies in Indonesia. The research method employed is normative legal research using legislative, conceptual, and legal policy approaches. The results of the study indicate that the legal policy of regulations on interfaith harmony still tends to prioritize social stability over the equal protection of citizens’ constitutional rights. Therefore, religious moderation needs to be adopted as a legal policy paradigm to develop regulations that are more inclusive, tolerant, democratic, and human rights-based in maintaining interfaith harmony in Indonesia